Biological Posts: Natural Alternatives in Restoring Smile - Azad, Antriksh; Chourasia, Hemant R; Hema, BS; Sharma, Ipsita; Bhartia, Rahul; Raghuvanshi, Rohit (Journal of Orofacial Research, 2015)
Traumatic injuries leading to severely mutilated anterior teeth are common in dentistry. These injuries may leave a severe impact when they affect  ndodontically treated teeth as strength of such teeth is compromised. Proper functional and esthetic rehabilitation of such badly broken teeth is a challenge. Dealing with the patient’s mental suffering and their impatience to regain the natural smile back makes the treatment even more challenging. An effective treatment plan including a suitable and cost-effective choice of post is very much necessary in such conditions. Biological posts obtained through extracted teeth from another individual represent an economic option and alternative technique for the functional recovery of extensively damaged teeth. All-ceramic crowns further add to enhanced esthetics. This paper presents a case where biological posts with composite core build up followed by all-ceramic crown adaptation have been used with successful outcome